Efektifitas Plat Ekspansi dan Simple Spring - Paryontri, Bayu Ananda; Wardani, Novia Silla (Fakultas Kedokteran Gigi Universitas Jember, 2024)
Improving occlusion and tooth alignment can be achieved through orthodontic treatment. Orthodontic appliances can also correct crowded teeth, which are common in Indonesia. The aim of this study is to assess the effectiveness of using expansion plates to create space and simple springs to correct the malposition of anterior teeth in the upper and lower jaws, specifically teeth 11, 31, and 41. A 22-year-old female patient with an overjet of 4.2 mm and an overbite of 2.7 mm. First molar relationship on the right and left sides: Angle's Class I. Canine relationship on the right and left sides: Class I. Malposit ion of the patient's individual teeth: 11 (distolabioversion), 15 (mesiopalatotorsion), 23 (mesiolabioversion), 25 (mesiopalatotorsion), 31 (mesiolingualversion), 33 (mesiolabiotorsion), and 41 (distolabioversion). Lateral expansion of 0.85 mm will be performed and tooth malpositions will be corrected using an active plate in the form of a simple spring on teeth 11, 21, 31, and 41. Tooth malpositions on elements 11 distolabioversion (corrected), 31 mesiolingualversion (corrected), and 41 distolabioversion (corrected). During visits 16 to 20, the operator performed retraction by activating a labial arch. There was a change in overjet from 4.2 mm to 3.15 mm. The treatment was effective in correcting the malposition of teeth 11, 31, and 41. The patient exhibited tooth movement mesially towards the labial direction, thus correcting the patient's teeth towards the ideal position.